Development of an Integrated Web-Based Quality Control Dashboard for Automated Sorting Data Monitoring - Yusmadi, Yudies; Pramudito, Dendy K; Muhidin, Asep (Jurnal Informatika Ekonomi Bisnis, 2025)
This study supports the development of a web-based Quality Control (QC) dashboard designed to improve the monitoring of product sorting data in manufacturing process. The impetus comes from the fact that traditional methods of capturing data by hand are very likely to be incorrect, slow, and cause problems with managing data. Currently, sorting results are still written down on physical log sheets which often leads to delays in reporting, puts records at risk of being lost or destroyed, and makes it harder to analyze data in real time. The study uses the Agile Development method to fix these problems, with a focus on iterative design, getting input from stakeholders, and making improvements all the time. The proposed dashboard will include several basic features, such as the ability to enter sorting results digitally, interactive data visualization in both graphical and tabular formats, automatic quality control report generation, and user management through role-based access control. These features are expected to turn data into useful information, which will allow the QC team to quickly make decisions based on evidence that enhance product quality. Web programming utilizes modern web technologies such as Laravel framework for backend processing, JavaScript, HTML, CSS, and Bootstrap to make responsive the user interface. Utilization of open-source technologies is meant to ensure that the system may grow and be maintained while keeping installation costs low.